2021
DOI: 10.33448/rsd-v10i15.22726
|View full text |Cite
|
Sign up to set email alerts
|

Age and sex estimation using fractal analysis in Brazilian adults: a discriminant analysis

Abstract: This study assessed the accuracy of fractal analysis (FA) to estimate chronological age and sex in Brazilian adults for forensic investigations. The gender-balanced sample comprised lateral cephalometric radiographs of 120 individuals, stratified according to age (20-29, 30-39, 40-49, 50-59 years) and sex (female and male). A trained calibrated examiner measured the fractal dimension (FD) of the mandibular ramus and mandibular angle. Linear regression and multiple logistic discriminant analysis were carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…It has been shown that real systems exhibit nonlinear behaviors (Garcia‐Ruiz et al, 2012; Meakin, 1998), examples of fields where these behaviors can be observed are: pluvimetry (García‐Marín, 2007), texture food (Serrano et al, 2019), medical signal and image analysis (Baish & Jain, 2000; dos Santos Menezes et al, 2021; Hua et al, 2009; Jud et al, 2016; Lopes & Betrouni, 2009; N'Diaye et al, 2013; Reishofer et al, 2018; Silvetti & Delrieux, 2010), and porous media (Ehlers & Wagner, 2019; Jiang & Tchelepi, 2019; Shen et al, 2018) the latest one is of our interest. Actually, scientific communications on porous systems cover multiple disciplines of science and engineering, some examples are: materials science and fluid dynamics (Calvo‐Guirado et al, 2019; Ehlers & Wagner, 2019; Hosseinikhah et al, 2020) thermodynamics (Alizadeh et al, 2021; Sheikholeslami et al, 2019) and biological systems (Khazayinejad et al, 2021; Kosari & Vafai, 2021), for instance; bones (Alves et al, 2017; Borowska et al, 2015; Camargo et al, 2016; Harrar et al, 2011; Hua et al, 2009; Koh et al, 2012; Sanchez‐Molina et al, 2013; Xiao et al, 2020; Zehani et al, 2016) and teeth (Nezafat et al, 2019; Solaymani et al, 2018, 2020)—on which we focus on.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that real systems exhibit nonlinear behaviors (Garcia‐Ruiz et al, 2012; Meakin, 1998), examples of fields where these behaviors can be observed are: pluvimetry (García‐Marín, 2007), texture food (Serrano et al, 2019), medical signal and image analysis (Baish & Jain, 2000; dos Santos Menezes et al, 2021; Hua et al, 2009; Jud et al, 2016; Lopes & Betrouni, 2009; N'Diaye et al, 2013; Reishofer et al, 2018; Silvetti & Delrieux, 2010), and porous media (Ehlers & Wagner, 2019; Jiang & Tchelepi, 2019; Shen et al, 2018) the latest one is of our interest. Actually, scientific communications on porous systems cover multiple disciplines of science and engineering, some examples are: materials science and fluid dynamics (Calvo‐Guirado et al, 2019; Ehlers & Wagner, 2019; Hosseinikhah et al, 2020) thermodynamics (Alizadeh et al, 2021; Sheikholeslami et al, 2019) and biological systems (Khazayinejad et al, 2021; Kosari & Vafai, 2021), for instance; bones (Alves et al, 2017; Borowska et al, 2015; Camargo et al, 2016; Harrar et al, 2011; Hua et al, 2009; Koh et al, 2012; Sanchez‐Molina et al, 2013; Xiao et al, 2020; Zehani et al, 2016) and teeth (Nezafat et al, 2019; Solaymani et al, 2018, 2020)—on which we focus on.…”
Section: Introductionmentioning
confidence: 99%